Association between intradialytic hypotension and physical function in patients undergoing maintenance hemodialysis: a multicenter cross-sectional study - Hou, Chun Qi; Luo, Xi Ju; Xu, Qin Juan; Zhi, Min; Liu, Min; Deng, Si Yan; Wang, Su Su; Hu, Hua Gang (Frontiers in Medicine, 2025)
Background and objectivesThe progressive decline in physical function is associated with a reduced quality of life and an increased risk of adverse clinical outcomes among patients undergoing maintenance hemodialysis (MHD). Intradialytic hypotension (IDH) has been identified as an independent risk factor for higher mortality and hospitalization rates in MHD patients. Nevertheless, the relationship between IDH and physical function in this population remains poorly understood. This study aimed to investigate the relationship between IDH and objectively assessed physical function in MHD patients.MethodsThis cross-sectional study was carried out in five blood purification centers in Suzhou, China, from March to July 2023. Physical function was assessed using a battery of test, including the six-minute walk test (6MWT), the 10-repetition sit-to-stand-to-sit test (STS10), the 30-s sit-to-stand-to-sit test (STS30), handgrip strength (HGS), and the timed up-and-go test (TUG). Intradialytic blood pressure data were retrospectively extracted from the electronic medical record system prior to the physical function assessments, encompassing 36 consecutive hemodialysis sessions for each patient. Multiple linear and Poisson regression analyses were performed to explore the association between the frequency of IDH and physical function. This study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology checklist for reporting observational research.ResultsThe study included 193 participants, of whom 67.9% were male, with a mean age of 53.3 years (SD = 12.6). The overall incidence of IDH was 13.7% across all hemodialysis sessions analyzed. After adjustment for potential confounders, multivariable regression analyses revealed that the higher frequency of IDH was significantly associated with poorer performance of the 6MWT (unstandardized coefficients [B] and 95% confidence interval [CI]: −2.715, −4.111 to −1.319 meters), the STS30 (−0.005, −0.009 to 0.000 repetitions), and HGS (−0.127, −0.236 to −0.018 kilograms). Conversely, more frequent IDH episodes were associated with the longer completion time in the STS10 (0.112, 0.004 to 0.220 s) and the TUG (0.033, 0.003 to 0.063 s).ConclusionA significant inverse relationship was found between the higher IDH frequency and worse physical function in MHD patients, manifested by impaired walking ability, reduced upper and lower limb muscle strength, and diminished mobile balance ability. These findings suggest that optimized blood pressure management during hemodialysis to minimize IDH occurrence could potentially preserve physical function in this population.